SWOT-AHP integration for determining development strategy of Pangkep Pomelo Citrus Agro-industry - Makkulawu, Andi Ridwan; Soemarno, Soemarno; Santoso, Imam; Mustaniroh, Siti Asmaul (Edelweiss Applied Science and Technology, 2024)
This research proposes a development strategy for the Pomelo Citrus agro-industry in the Pangkep Regency, utilising a combined SWOT and Analytical Hierarchy Process (AHP) approach. The purpose of this study is to identify key factors influencing the industry's competitiveness and growth potential, providing a strategic framework for stakeholders. The methodology involves SWOT analysis to evaluate internal and external factors, followed by AHP to prioritise these factors for strategic decision-making. Findings indicate that strengths and opportunities are the most influential factors, with abundant raw materials and strong government support as major growth drivers. In contrast, limitations in technological mastery and the threat of land-use changes present relevant but less significant challenges. The SWOT quadrant analysis places the Pangkep Pomelo agro-industry in Quadrant I (Growth), suggesting a strategy focused on expansion, capacity building, innovation, and market utilisation. The conclusion underscores that a growth-oriented strategy can enhance regional economic resilience by maximising the value of local commodities. Practical implications of this study include actionable insights for policymakers and business actors to leverage local strengths and address constraints, promoting sustainable development in the agro-industry sector.